Femtosecond laser ablation of cadmium tungstate for scintillator arrays. (August 2016) - Richards, S.; Baker, M.A.; Wilson, M.D.; Lohstroh, A.; Seller, P.
Abstract: Ultrafast pulsed laser ablation has been investigated as a technique to machine CdWO4 single crystal scintillator and segment it into small blocks with the aim of fabricating a 2D high energy X-ray imaging array. Cadmium tungstate (CdWO4 ) is a brittle transparent scintillator used for the detection of high energy X-rays and γ-rays. A 6 W Yb:KGW Pharos-SP pulsed laser of wavelength 1028 nm was used with a tuneable pulse duration of 10 ps to 190 fs, repetition rate of up to 600 kHz and pulse energies of up to 1 mJ was employed. The effect of varying the pulse duration, pulse energy, pulse overlap and scan pattern on the laser induced damage to the crystals was investigated. A pulse duration of ≥500 fs was found to induce substantial cracking in the material. The laser induced damage was minimised using the following operating parameters: a pulse duration of 190 fs, fluence of 15.3 J cm −2 and employing a serpentine scan pattern with a normalised pulse overlap of 0.8. The surface of the ablated surfaces was studied using scanning electron microscopy, energy dispersive X-ray spectroscopy, atomic force microscopy and X-ray photoelectron spectroscopy. Ablation products were found to contain cadmium tungstate together with different cadmium and tungsten oxides. These laser ablation products could be removed using an ammonium hydroxide treatment. Highlights: Femtosecond ablation was used to machine a brittle dielectric for a γ-ray imager. Laser induced cracking was thought to be thermally induced. EDS showed a change in the Cd:W ratio with ablated depth. XPS showed the laser induced the formation of non-stoichiometric compounds. Ammonium hydroxide was used to remove the undesirable compounds from the surface.